2005
DOI: 10.1007/s10800-005-6722-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Novel Composite Material Based on a Nafion® Membrane and Polypyrrole for Potential Application in a PEM Fuel Cell

Abstract: The process of embedding polypyrrole (PPy) on the surface of a Nafion Ò membrane was studied. Three methods of PPy synthesis directly on the membrane surface were compared. The diffusion method based on the separation of monomer and oxidant (peroxidisulphate) solutions by the membrane to be modified is proposed as the most promising one. The monomer diffuses through the membrane to the oxidant side, where it is polymerized. In this case sulphate is incorporated into the film as a counter-ion. PPy film prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…The electrocatalytic activity of the film is documented by the cyclic voltammetric polarization curves shown in Figure 6. It was found that a charge corresponding to the redox processes in the PPy film increased linearly with its thickness [9]. This offers an opportunity for a fast, nondestructive, in situ rough estimate of the synthesized film thickness.…”
Section: Nafion ò /Cp Composite Synthesismentioning
confidence: 92%
See 3 more Smart Citations
“…The electrocatalytic activity of the film is documented by the cyclic voltammetric polarization curves shown in Figure 6. It was found that a charge corresponding to the redox processes in the PPy film increased linearly with its thickness [9]. This offers an opportunity for a fast, nondestructive, in situ rough estimate of the synthesized film thickness.…”
Section: Nafion ò /Cp Composite Synthesismentioning
confidence: 92%
“…A diffusion method for synthesis of CP directly on the PEM surface was proposed as an alternative approach [9] based on the work of Hsu [10]. A broader characterization of these composites is still missing.…”
Section: Indices and Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polypyrrole can be obtained by chemical or electrochemical synthesis [12][13][14][15][16]. Chemical polymerization makes it possible to form PPy coatings on the objects of different geometry (microspheres, solid, and porous films, etc.)…”
Section: Synthesis and Structure Of The Composite Materialmentioning
confidence: 99%